Analisis Kedisiplinan Crew dan Perawatan Grab terhadap Kelancaran Pemuatan di MV. Natascha - Pramudita, Andre Eka; Sa'adah, Nor; Budi Hartanto, Cahya Fajar (JURNAL BARTEK, 2026)
The smoothness of loading via sea transportation is greatly influenced by the discipline of the ship's crew and the condition of loading and unloading equipment such as grabs. However, on the MV Natascha, there are still obstacles in the form of damaged grabs and suboptimal crew discipline, which hinder the smooth loading process. This study aims to analyze the effect of crew discipline and grab maintenance on loading smoothness at MV. Natascha. The research employed a quantitative method, involving 23 ship crew members as respondents. Data were collected through observations and questionnaires, and analyzed using multiple linear regression with SPSS 25. The results indicate that crew discipline has a positive and significant effect on loading smoothness with a significance value of 0.002 < 0.05. Grab maintenance also shows a positive and significant effect with a significance value of 0.004 < 0.05. Simultaneously, crew discipline and grab maintenance contribute 73.5% to loading smoothness, while the remaining 26.5% is influenced by other factors outside this study. These findings highlight the importance of disciplined human resources and regular equipment maintenance to improve efficiency and ensure smooth loading operations on bulk carrier vessels.